Climate change, agriculture, and food security in Tanzania - Channing Arndt; Will Farmer; Ken Strzepek; James Thurlow (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
The consequences of climate change for agriculture and food security in developing countries are of serious concern. Due to their reliance on rain-fed agriculture both as a source of income and consumption, many low-income countries are generally considered to be most vulnerable to climate change. Here, we estimate the impact of climate change on food security in Tanzania. Representative climate projections are used in calibrated crop models to predict crop yield changes for 110 districts in Tanzania. These results are in turn imposed on a highly-disaggregated, dynamic economy-wide model of Tanzania. We find that, relative to a no climate change baseline and considering domestic agricultural production as the principal channel of impact, food security in Tanzania appears likely to deteriorate as a consequence of climate change. The analysis points to a high degree of diversity of outcomes (including some favourable outcomes) across climate scenarios, sectors, and regions. The economic modelling indicates that markets have the potential to smooth outcomes on households across regions and income groups, though noteworthy differences in impacts across households persist both by region and by income category.
Keywords: Q1; Q54; 330; climate change; agriculture; food security; crop model; CGE model; Tanzania; Klimaveränderung; Agrarproduktion; Nahrungsmittelversorgung; CGE-Modelling; Tansania